Enzymology of the Anaphase‐Promoting Complex - Carroll, Christopher W.; Morgan, David O. (Methods in Enzymology, 2005)
The anaphase‐promoting complex (APC) is an ubiquitin‐protein ligase that promotes mitotic progression by catalyzing the ubiquitination of numerous proteins, including securin and cyclin. Its complex subunit composition and extensive regulation make the APC an active subject of investigation for both cell biologists and enzymologists. This chapter describes a system for the reconstitution and quantitative analysis of APC activity from budding yeast in vitro. We focus in particular on the measurement of processive ubiquitination, which complements traditional analysis of the reaction rate as a means to elucidate the molecular details of substrate recognition and ubiquitination by the APC.